1994
DOI: 10.1161/01.cir.89.6.2552
|View full text |Cite
|
Sign up to set email alerts
|

Predicting recovery of severe regional ventricular dysfunction. Comparison of resting scintigraphy with 201Tl and 99mTc-sestamibi.

Abstract: In patients with coronary artery disease and left ventricular dysfunction, quantified sestamibi activity 1 hour after rest injection parallels redistribution 201Tl activity after a resting injection, suggesting that uptake and subsequent handling of sestamibi are more complex than can be explained by a pure flow tracer with no redistribution. Quantitative analysis of regional activities of both 201Tl and sestamibi after resting injections can differentiate viable from nonviable myocardium, and the two agents c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
6

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 354 publications
(123 citation statements)
references
References 31 publications
5
111
1
6
Order By: Relevance
“…The predictive values of AUC, sensitivity and specificity were comparable or slightly lower than the precedent investigations [5,8,12]. However, ours were comparable with the results by Acampa et al using sublingual nitrate administration [9].…”
Section: Characteristics Of the Present Studysupporting
confidence: 87%
See 4 more Smart Citations
“…The predictive values of AUC, sensitivity and specificity were comparable or slightly lower than the precedent investigations [5,8,12]. However, ours were comparable with the results by Acampa et al using sublingual nitrate administration [9].…”
Section: Characteristics Of the Present Studysupporting
confidence: 87%
“…Mean EFs were 34±10% by Udelson et al [8] and 36±9% by Kang et al [12], and those in most studies were from 30% to 50% [5]. In contrast, our study population showed mean EF of 50% and mean EDV of 103 mL before revascularization, average segmental %uptake of 66% and 55% for improved and non-improved groups, and mean visual perfusion defect score of 1 and 1.3 for improved and non-improved groups, respectively.…”
Section: Characteristics Of the Present Studycontrasting
confidence: 59%
See 3 more Smart Citations